Successful treatment of a Candida auris intra-articular infection - Scott C. Roberts; Teresa R. Zembower; Maureen K. Bolon; Anish R. Kadakia; Jasen H. Gilley; Jason H. Ko; Jessica Clark; Sharon Ward-Fore; Babafemi O. Taiwo (Emerging Microbes and Infections)
A 78-year-old woman with a long-term ankle spacer with antibacterials developed an intra-articular Candida auris infection. Treatment with systemic antifungal therapy plus an amphotericin B moulded cement spacer was successful.